CHALLENGES AND EXPORT STRATEGIES OF INDONESIA - Mangani , Ktut Silvanita (Fundamental Management Journal, 2020)
Exports are economic activities that can increase growth. However, during the ten years from 2018, the Indonesian economy to ASEAN experienced a growing deficit. The same thing happened in Indonesia's exports in total. The slowdown could occur due to a decrease in export volume and price decline. Therefore, this condition becomes a challenge for Indonesia's foreign trade. The problem becomes more severe for SMEs. Thus, efforts or strategies are needed to increase Indonesia's exports to ASEAN and the world. This paper is a simple study of the challenges and strategies of Indonesia's exports. Keywords :Export,Challenge,Strategy,ASEAN